Perancangan Ulang Tata Letak Fasilitas Produksi Menggunakan Metode Fraktal di Manufaktur Spare Part - Yoela Senni Stefianti; Rainisa Maini Heryanto; Kartika Suhada (Universitas Medan Area, 2022)
The relayout of the production facilities needs to be carried out by a manufacturer if there is a new product produced that has a different material flow from the existing product. If the layout of the initial facility is maintained, the material flow will become irregular and lead to long material transfer distances and substantial material handling costs. One method that can be used for relayout production facilities is the fractal method. This method is suitable for job shop system because it could provide a high level of flexibility and low total material handling costs. The case study used in this research, which is a spare part manufacturer that initially applied the by-process layout. The initial layout is less flexible in line with the current manufacturing conditions where there are additional variations in the types of products produced. The distance between machines with different types becomes far apart. By relayout of the production facilities using the fractal method, the material handling cost savings of IDR 157,868.64/week or 60.75%/week and the total savings in moving distance is 186,365 meters/week or 38.93%/week. Fractal method is proven to be used to design the layout of production facilities and reduce material handling costs and material transfer distances.